Moxifloxacin in the Outpatient Treatment of Moderate Exacerbations of Chronic Obstructive Pulmonary Disease - Minov, Jordan; Stoleski, Sasho; Petrova, Tatjana; Vasilevska, Kristin; Mijakoski, Dragan; Karadzinska-Bislimovska, Jovanka (ID Design Press/Scientific Foundation SPIROSKI, 2018)
Bacterial infections are involved in more than a half of the exacerbations of chronic obstructive pulmonary disease (COPD).
Keywords: Antibiotic; Bacterial infection; Chronic obstructive pulmonary disease; Clinical success; Exacerbation; Side effects